What Are the Patient Privacy Concerns in AI Telemedicine? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The integration of Artificial Intelligence (AI) into telemedicine has heralded a new era of healthcare delivery, offering unprecedented opportunities for rem...
Keywords: Telemedicine and Digital Health; Patient; Privacy; Concerns; Artificial Intelligence; Healthcare